2020
DOI: 10.3390/healthcare8040513
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Autologous Micrografts Technology in Combination with Negative Pressure Wound Therapy (NPWT) for Quick Granulation Tissue Formation in Chronic/Refractory Ulcer

Abstract: Negative pressure wound therapy (NPWT) has been commonly used over the years for a wide range of chronic/refractory lesions. Alternatively, autologous micrografting technology is recently becoming a powerful modality for initiating wound healing. The case presented is of a patient with a lower leg ulcer that had responded poorly to NPWT alone for three weeks. Consequently, the patient was put on a combination therapy of NPWT and micrografting. After injection of a dermal tissue micrografts suspension into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The wound healing process includes bleeding, inflammatory reaction, granulation tissue formation, and tissue remodeling, which is a dynamic, orderly, and interlacing process. However, this process may be destroyed under the action of various internal and external factors, resulting in the pathological inflammatory reaction, and ultimately leading to chronic refractory wounds ( Takagi et al, 2020 ). The clinical characteristics of refractory wounds mainly include tissue defects caused by severe trauma, severe infection on the wound, impairment of microcirculation on the wound and its surroundings, and severe underlying diseases or poor nutritional status ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The wound healing process includes bleeding, inflammatory reaction, granulation tissue formation, and tissue remodeling, which is a dynamic, orderly, and interlacing process. However, this process may be destroyed under the action of various internal and external factors, resulting in the pathological inflammatory reaction, and ultimately leading to chronic refractory wounds ( Takagi et al, 2020 ). The clinical characteristics of refractory wounds mainly include tissue defects caused by severe trauma, severe infection on the wound, impairment of microcirculation on the wound and its surroundings, and severe underlying diseases or poor nutritional status ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to delivery of biologics, physical treatment approaches such as hyperbaric oxygen therapy, low-level laser therapy and electrical stimulation were attempted to accelerate the healing of chronic ulcers, although with inconsistent success [ 168 ]. Negative pressure wound therapy (NPWT), also known as vacuum-assisted closure, is another physical treatment approach, which is based on differential suction or vacuum creation onto the wounds to enhance fluid removal, reduce edema and alter the wound microenvironment [ 169 ]. NPWT demonstrated promising results in accelerating the healing of lower-limb ulcers of vascular origin, such as DFU.…”
Section: Modulation Of the Immune System To Improve Wound Healingmentioning
confidence: 99%
“…25 A patient with a lower ulcer spent 3 weeks poorly responding to NPWT alone, however when used in combination with injection of dermal tissue micrografts in the wound bed, the healing cascade and rapid granulation tissue formation resulted. 25 Micrografting techniques applied to dorsal wounds of mice have been shown to augment epithelization with regeneration and migration. 26 Another study demonstrated that in lower limb wounds, novel autologous micrografts from Rigenera technology induced complete reconstructive healing for 69 patients within up to 12 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Micrografts, used in combination with negative pressure wound therapy (NPWT), been shown to enhance tissue granulation and regeneration 25 . A patient with a lower ulcer spent 3 weeks poorly responding to NPWT alone, however when used in combination with injection of dermal tissue micrografts in the wound bed, the healing cascade and rapid granulation tissue formation resulted 25 . Micrografting techniques applied to dorsal wounds of mice have been shown to augment epithelization with regeneration and migration 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation